PEMBAGIAN WARIS SAMA RATA ANAK LAKI-LAKI DAN PEREMPUAN PERSPEKTIF MASLAHAT DAN KEADILAN ISLAM: Analisis putusan 3052/Pdt.G.2010/PA.Kab.Malang - Muhammad Nasrulloh; Doli Witro (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The Religious Court of Malang Regency decided to divide the inheritance equally between sons and daughters. This certainly deviates from the sound of Article 176 KHI and the Koran in Surah an-Nisa’ verse 11, which states that the male share is two to one female share. The judge’s decision was based on the hadith of the apostle, which reads equalize in giving to sons and daughters and refers to article 183, which contains peace in distribution. This research is analysis-based normative research that seeks to examine the decisions of the Religious Courts in terms of benefits and Islamic justice. This study concludes that the judge’s decision is weak. Because the basis of the argument for article 183 is final and binding. At the same time, this case did not find a consensus. In addition, there has been no elaboration regarding the share of each heir before the agreement as mandated by Article 183. The judge’s decision is classified as biased because it annulled the principle of balanced justice without being confirmed by social facts and family culture. Judges tend to beat the average regardless of the attributes of the family heirs. This further strengthens the judge’s decision which is easily broken if brought to the appeal table.